Evaluating the Safety of Oral Propranolol Therapy in Patients With PHACE Syndrome - Olsen, Gerilyn M. (JAMA Dermatol, 2020)
IMPORTANCE: Oral propranolol is widely considered to be first-line therapy for complicated infantile hemangioma, but its use in patients with PHACE (posterior fossa malformations, hemangioma, arterial anomalies, cardiac defects, eye anomalies) syndrome has been debated owing to concerns that the cardiovascular effects of the drug may increase the risk for arterial ischemic stroke. OBJECTIVE: To assess the incidence of adverse events among patients with PHACE syndrome receiving oral propranolol for infantile hemangioma. DESIGN, SETTING, AND PARTICIPANTS: This multicenter retrospective cohort study assessed the incidence of adverse events among 76 patients with PHACE syndrome receiving oral propranolol for infantile hemangioma at 11 tertiary care, academic pediatric dermatology practices. Medical records from January 1, 2010, through April 25, 2017, were reviewed. EXPOSURES: Patients received oral propranolol, 0.3 mg/kg/dose or more. MAIN OUTCOMES AND MEASURES: The main outcome was the rate and severity of adverse events occurring throughout the course of treatment with oral propranolol, as documented in the medical records. Adverse events were graded from 1 to 5 using a scale derived from the Common Terminology Criteria for Adverse Events and were considered to be serious if they were grade 3 or higher. RESULTS: A total of 76 patients (59 girls and 17 boys; median age at propranolol initiation, 56 days [range, 0-396 days]) met the inclusion criteria. There were no reports of serious adverse events (ie, stroke, transient ischemic attack, or cardiovascular events) during treatment with oral propranolol. A total of 46 nonserious adverse events were reported among 29 patients (38.2%); the most commonly reported nonserious adverse events were sleep disturbances and minor gastrointestinal tract and respiratory tract symptoms. In a comparison with 726 infants who received oral propranolol for hemangioma but did not meet criteria for PHACE syndrome, there was no significant difference in the rate of serious adverse events experienced during treatment (0 of 76 patients with PHACE syndrome and 3 of 726 patients without PHACE syndrome [0.4%]). CONCLUSIONS AND RELEVANCE: This study found that oral propranolol was used to treat infantile hemangioma in 76 patients with PHACE syndrome and that no serious adverse events were experienced. These data provide support for the safety of oral propranolol in this patient population.